A new complexity reduction scheme in selective mapping‐based visible light communication direct current‐biased optical orthogonal frequency division multiplexing systems. Issue 5 (29th June 2022) - Gunturu, Chakravarthy; Valluri, Sivaprasad
Abstract: Visible light communication (VLC) has emerged as a good accompaniment to radio‐frequency (RF) technologies by deploying multicarrier schemes such as orthogonal frequency division multiplexing (OFDM). However, the coherent summation of carriers in the OFDM system leads to a high peak‐to‐average‐power ratio (PAPR), causing non‐linear clipping distortion at the transmitting light‐emitting diode. This intricacy becomes a potential barrier for intensity modulation and limits the VLC systems' bandwidth. In the literature, non‐distorting PAPR lowering approaches, such as the selective mapping (SLM) approach, have been confirmed as the most effective strategy for reducing ineludible high PAPR in optical OFDM systems among all other available techniques. Besides its astounding performance, the computational complexity also becomes a major complication in SLM due to the generation of multiple candidates. This paper proposes a computational complexity minimisation approach using inherit system properties in the SLM‐based PAPR suppression method for VLC systems, where the phase sequence vectors are considered periodic. The alternative direct current‐biased optical orthogonal frequency division multiplexing candidates for the single frequency‐domain data block are generated with the periodic phase rotation vector. The evaluation of the complexity analysis and the simulation results shows that the mitigation of computational complexity surpasses the standard SLM technique.